Social relationships affect dispersal timing revealing a delayed infanticide in African lions. Issue 9 (3rd April 2014) - Elliot, Nicholas B.; Valeix, Marion; Macdonald, David W.; Loveridge, Andrew J.
<x xml:space="preserve">Abstract</x> Successful dispersal is a critical parameter for species persistence and evolution. Despite this, factors determining successful dispersal are poorly understood, particularly in wide‐ranging species. Condition‐dependent dispersal strategies tend to be more successful than fixed ones since they can entail dispersal occurring when an individual is most suited to doing so. However, the juvenile's family group or conspecifics may initiate premature dispersal, which could influence whether or not dispersal is successful. We studied dispersal in African lions and investigated 1) whether dispersal age affects dispersal success and 2) factors determining dispersal timing. We found that all males that dispersed before 31 months died during transience and that dispersal coincided, regardless of age or body condition, with the arrival of unfamiliar adult males. Whereas a high turn‐over of territorial males is known to result in infanticide and eviction of sub‐adults, our results indicate it can also induce a previously undescribed, 'delayed infanticide'.